Clustering Regions in West Sumatera Based on the Special Protection Index for Children Using K-Means Clustering with Silhouette Coefficient - Siti Nurhaliza; Tessy Octavia Mukhti (Departemen Statistika Universitas Negeri Padang, 2025)
Child protection is a crucial aspect of social development, especially in West Sumatra Province, which consists of 19 regencies/cities with diverse child protection characteristics. This study aims to cluster regencies/cities in West Sumatra based on the 2021 Child Special Protection Index (IPKA) using the K-Means Clustering method with the Silhouette Coefficient. Secondary data were obtained from the Office of Women's Empowerment and Child Protection, Population Control, and Family Planning (DP3AP2KB) of West Sumatra Province, covering variables such as the percentage of working children, internet access, education level, poverty, and child neglect. The results show that the K-Means method is effective in quickly and accurately grouping data into homogeneous clusters, while a Silhouette Coefficient value of 0.70 indicates a strong cluster structure and high-quality grouping.